Influenza-related healthcare visits, hospital admissions, and direct medical costs for all children aged 2 to 17 years in a defined Swedish region, monitored for 7 years. Issue 33 (August 2016) - Rahmqvist, Mikael; Gjessing, Kristian; Faresjö, Tomas
Abstract : Supplemental Digital Content is available in the text Abstract: Background: The seasonal variation of influenza and influenza-like illness (ILI) is well known. However, studies assessing the factual direct costs of ILI for an entire population are rare. Methods: In this register study, we analyzed the seasonal variation of ILI-related healthcare visits and hospital admissions for children aged 2 to 17 years, and the resultant parental absence from work, for the period 2005 to 2012. The study population comprised an open cohort of about 78, 000 children per year from a defined region. ILI was defined as ICD-10 codes: J00-J06; J09-J15, J20; H65-H67. Results: Overall, the odds of visiting a primary care center for an ILI was 1.64-times higher during the peak influenza season, compared to the preinfluenza season. The corresponding OR among children aged 2 to 4 years was 1.96. On average, an estimated 20% of all healthcare visits for children aged 2 to 17 years, and 10% of the total healthcare costs, were attributable to seasonal ILI. In primary care, the costs per week and 10, 000 person years for ILI varied – by season – from €3500 to €7400. The total ILI cost per year, including all physical healthcare forms, was €400, 400 per 10, 000 children aged 2 to 17 years. The costs for prescribed and purchased drugs related to ILI symptoms constituted 52% of all medicine costs, and added 5.8% to the direct healthcare costs. The use of temporary parental employment benefits for caring of ill child followed the seasonal pattern of ILI ( r = 0.91, P  < 0.001). Parental absence from work was estimated to generate indirect costs, through loss of productivity of 5.2 to 6.2 times the direct costs. Conclusions: Direct healthcare costs increased significantly during the influenza season for children aged 2 to 17 years, both in primary and hospital outpatient care, but not in hospital inpatient care. Primary care manages the majority of visits for influenza and ILI. Children 2 to 4 years have a larger portion of their total healthcare encounters related to ILI compared with older children. There is a clear correlation between ILI visits across the years and parental absence from work.